First In, First Out? How Debt Age Affects Debt Prepayment Decisions - Johnson, Alicia M.; Villanova, Daniel; Sevilla, Julio; Isaac, Mathew S.; Bagchi, Rajesh (Journal of Marketing Research, 2026)
Consumers often take on debt at different points in time. As a result, debts may be months, if not years, apart in age. In this research, the authors ask whether and how debt age affects installment debt prepayment decisions. While the ideal strategy for prepaying older versus newer debt depends on specific account parameters (e.g., interest rate, monthly payment), in many circumstances it is financially advantageous to prioritize paying down newer debt. This is because debt amortization (i.e., repayment) schedules often result in reduced interest payments when newer installment debts are paid first. However, across eight studies, including a secondary dataset of consumer loans, the authors find that consumers prefer to prepay older debt first—even when it is financially disadvantageous to do so. The authors refer to this as a FIFO (first-in, first-out) preference and demonstrate that consumers prioritize older versus newer debt prepayment because they feel they have invested greater effort (i.e., mental or physical work and energy) to repay it. Accordingly, reducing the effort required to repay an older debt (e.g., through automated payments) or shifting consumers’ focus from invested effort to remaining effort attenuates the FIFO preference. These findings offer implications for theory, managerial practice, and consumer welfare.